An Investigation of the Implications of Visual Impairment for Illumination Requirements. (March 2022) - Hauck, Nico; Mahdavi, Ardeshir
Introduction: The present contribution mainly focuses on the evaluation of the visual performance of people with impaired vision and, for comparison purposes, individuals with typical vision under different lighting conditions.Methods: A monitor with adjustable brightness facilitated various test runs to determine the visual performance as a function of the adaptation luminance and glare. In addition, the subjective impressions of the participants with impaired vision were queried via interviews. The study included 98 people with impaired vision and 38 people without visual impairments.Results: The interview results suggest that most people with visual impairments require special lighting conditions. An increased lighting requirement is observed amongst 50% of this group. Moreover, 75% of this group display increased glare sensitivity. Likewise, adaptation problems and critical issues related to nonuniform lighting are manifest. Individuals with impaired vision included in this study display a greatly reduced contrast threshold and a higher subjective level of discomfort compared to individuals with typical vision.Discussion: Most visually impaired participants state that they require a higher degree of brightness to achieve their maximum personal visual performance. However, about a quarter of the participants reported that they achieve a better visual performance at lower brightness, while displaying an increased sensitivity to glare. In general, glare has a decisive influence on the visual performance of the participants with impaired vision in our study.Implications for Practitioners: The study reconfirms the essential importance of glare-free and uniform general lighting strategies (e.g., via predominantly indirect lighting) as well as avoiding abrupt spatiotemporal luminance changes (e.g., via provision of a transition zone between locations with very different luminance levels).